Intrauterine programming of lipid metabolic alterations in the heart of the offspring of diabetic rats is prevented by maternal diets enriched in olive oil - Capobianco, Evangelina Lorena (2015)
Scope: Maternal diabetes can program metabolic and cardiovascular diseases in the offspring. The aim of this work was to address whether an olive oil supplemented diet during pregnancy can prevent lipid metabolic alterations in the heart of the offspring of mild diabetic rats. Methods and results: Control and diabetic Wistar rats were fed during pregnancy with either a standard diet or a 6% olive oil supplemented diet. The heart of adult offspring from diabetic rats showed increases in lipid concentrations (triglycerides in males and phospholipids, cholesterol, and free fatty acids in females), which were prevented with the maternal diets enriched in olive oil. Maternal olive oil supplementation increased the content of unsaturated fatty acids in the hearts of both female and male offspring from diabetic rats (possibly due to a reduction in lipoperoxidation), increased the expression of Δ6 desaturase in the heart of male offspring from diabetic rats, and increased the expression of peroxisome proliferator activated receptor α in the hearts of both female and male offspring from diabetic rats. Conclusion: Relevant alterations in cardiac lipid metabolism were evident in the adult offspring of a mild diabetic rat model, and regulated by maternal diets enriched in olive oil.